Public money for public goods: Winners and losers from CAP reform - Valentin Zahrnt (European Centre for International Political Economy (ECIPE), 2009)
To attain fundamental reform of the post-2013 Common Agricultural Policy (CAP), a serious debate is needed in 2009/10 that prepares the decisions to be taken in 2011/12. The paper contributes to this debate, first, by arguing that the Single Farm Payment should not become the mainstay of the future CAP but be gradually phased out. Second, it proposes that the existing two-pillar structure of the CAP should be replaced by a public goods pillar (containing all efficient policies to be preserved) and a discretionary pillar (encompassing all inefficient policies to be removed over time). This would give member states flexibility in how they phase out inefficient policies, while the EU reform agenda would not be clogged with the contentious details of their progressive removal. Third, the paper assesses the criteria likely to guide future allocation of CAP payments, such as GDP per capita, agricultural and forest areas, and areas with Natura 2000 status. Fourth, it estimates member states' share in total CAP payments under different post-2013 scenarios. This reveals surprising differences between the negotiating positions that countries traditionally adopt and the payment receipts they can expect from reform.
Keywords: 330; EU-Agrarpolitik; Agrarsubvention; Reform; Gemeinsame Marktorganisation; EU-Staaten